Acoustical properties of 3D printed thermoplastics - Antoniou, Anastasia; Evripidou, Nikolas; Giannakou, Marinos; Constantinides, Georgios; Damianou, Christakis A. (My University, 2021)
With focused ultrasound (FUS) gaining popularity as a therapeutic modality for brain diseases, the need for skull phantoms that are suitable for evaluating FUS protocols is increasing. In the current study, the acoustical properties of several three-dimensional (3D) printed thermoplastic samples were evaluated to assess their suitability to mimic human skull and bone accurately. Samples were 3D printed using eight commercially available thermoplastic materials. The acoustic properties of the printed samples, including attenuation coefficient, speed of sound, and acoustic impedance, were investigated using transmission-through and pulse-echo techniques. The ultrasonic attenuation, estimated at a frequency of 1.1 MHz, varied from approximately 7 to 32 dB/cm. The frequency dependence of attenuation was described by a power law in the frequency range of 0.2-3.5 MHz, and the exponential index of frequency was found to vary from 1.30 to 2.24. The longitudinal velocity of 2.7 MHz sound waves was in the range of 1700-3050 m/s. The results demonstrate that thermoplastics could potentially be used for the 3D construction of high-quality skull phantoms.
Keywords: Focused ultrasound; Skull phantoms; Acoustic impedance; Bone; Phantoms; Reinforced plastics; Thermoplastics